Smarandache Rings and Smarandache Elements - Parween Hummadi; Shadan Osman (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we study some Smarandache (S) notions in some types of   rings. Conditions are given under which   is a Smarandache ring. We study Smarandache ideals, Smarandache subrings and Smarandache weakly Boolean   rings. We discuss some types of Smarandache elements in rings. Moreover, we get some other results.